THE EFFECT OF ACIDIFICATION ON GROWTH AND PHOTOSYNTHESIS RATE OF SEAGRASS Thalassia hemprichii (Ehrenberg.) Ascherson (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Seagrass is a water plant that has flowers and ability to adapt to live and grow in the sea like a terrestrial plant. The survival of seagrass is greatly influenced by physical and chemical parameters of waters, such as pH, temperature, and salinity. The Intergovernmental Panel on Climate Change (IPCC) report by the end of 21st century, CO2 in the atmosphere has doubled along with the industrial development. The increase in CO2 in the atmosphere causes ocean acidification, it can change the chemical structure and decrease the pH of sea water. The low pH of sea water influences plant phisiology such as the inhibition of photosynthesis and growth. The purpose of this study is to examine the effect of pH on the growth and photosynthesis rate of seagrass Thalassia hemprichii. The study used Completely Randomized Design with 3 treatments control (8.10-8.50), medium pH (7.76-8.00) and low pH (7.50-7.75) in 5 replicates. The results showed that growth rate, photosynthetic rate and chlorophyll content has a bigger value on control treatment than the low pH treatment. The ANOVA test results were not significant for all treatment variables and had a negative impact on the survival of seagrass.